The Umru’ul-Qais Flirtation Stanzas to Unaizah in the Poetry Al-Mu'allaqat (Michael Riffaterre's Semiotic Analysis) - Sudarmawan, Habib Muharrom; Adelawati, Munzila (Universitas Ahmad Dahlan, 2024)
Al-Mu'allaqāt is the most famous Arabic poem of the pre-Islamic period. Al-Mu'allaqat often uses flirting as one of its themes, and Umru’ul-Qays' al-Mu'allaqat is no exception. It is addressed to his lover, Unaizah. It is often regarded as an expression of the poet's love for his beloved, but like any other poem, the flirtation stanzas in Umru'ul-Qays' al-Mu'allaqat also expresses meaning in the indirect ways. The purpose of this study is to determine the meaning of Umru'ul-Qays' flirtation stanzas in Al-Mu'allaqat. This research applies Michael Riffaterre's semiotic theory and implements his methods, such as heuristic reading, hermeneutic reading, searching for matrix, model, variant, and hypogram. The data source is the flirtation stanzas to Unaizah in the poetry Al-Mu'allaqāt by Umru’ul-Qays. This research is to understand the meaning and social context of Arabic literary works, as well as to dissect the variations of the sayings used by Umru'ul-Qays for Unaizah, which reflect the unrequited love between the two. The results of this research are that the flirtation stanzas in Al-Muallaqat by Umru’ul-Qays also expresses meaning in an indirect way. This poem also describes Umru'ul Qays' deep love even though he was rejected many times.